Digital health outreach to promote postpartum screening after gestational diabetes: A randomized factorial pilot study - Susan D. Brown; Brittany L. Garcia; Jenna L. Ritchie; Ai-Lin Tsai; Andrea Millman; Mara Greenberg; Charles P. Quesenberry; Assiamira Ferrara (Elsevier, 2024)
Objective: We examined the acceptability and feasibility of a multi-component digital health outreach intervention to promote uptake of guideline-recommended postpartum screening for type 2 diabetes among patients with gestational diabetes (GDM). Methods: We conducted a 24 randomized factorial experiment as part of the Multiphase Optimization Strategy (MOST) preparation phase for developing behavioral interventions. Participants with current or recent GDM in an integrated healthcare system were randomized to receive an outreach message with up to four intervention components, designed to be self-administered in about 10 min and efficiently delivered online via REDCap: a streamlined values affirmation, personalized information on diabetes risk, an interactive motivational interviewing-based component, and an interactive action planning component. Patient-reported acceptability and feasibility outcomes were assessed via survey. Results: Among 162 participants, 72% self-identified with a racial/ethnic minority group. Across components, acceptability scores averaged 3.9/5; ≥91% of participants read most or all of the outreach message; ≥89% perceived the amount of information as "about right"; and ≥ 87% completed ≥1 interactive prompt. Conclusion: Each intervention component was acceptable to diverse patients and feasible to deliver in a brief, self-directed, online format. Innovation: These novel components target unaddressed barriers to patient engagement in guideline-recommended postpartum diabetes screening and adapt theory-based behavior change techniques for large-scale use.